Desorption of Copper from Soil and Sediment - Jopony, Marcus (1986)
Copper desorption isotherms for three soil and sediment samples obtained from the Lohan area in Ranau, Sabah were determined. There was large hysteresis in the desorption isotherms, showing irreversible retention of adsorbed copper. The deso1'bability of the adsorbed copper was found to be very small at low levels of Cu adsorption compared with higher levels.